2006
DOI: 10.1158/1055-9965.epi-06-0038
|View full text |Cite
|
Sign up to set email alerts
|

Use of Analgesics and Nonsteroidal Anti-inflammatory Drugs, Genetic Predisposition, and Bladder Cancer Risk in Spain

Abstract: Background: We assessed use of nonaspirin nonsteroidal anti-inflammatory drugs (NSAID), aspirin, paracetamol (acetaminophen), phenacetin, and metamizol (dipyrone) and risk of bladder cancer and their interaction with polymorphisms in drug-metabolizing genes. Methods: We analyzed personal interview data from 958 incident bladder cancer cases and 1,029 hospital controls from a multicenter case-control study in Spain. A drug matrix was developed to estimate cumulative lifetime dose of active ingredients. Polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 44 publications
2
37
0
1
Order By: Relevance
“…Formation of n-nitroso compounds (noc) by reaction with nitrite has been found to occur for diclofenac, metamizole, indomethacin, and paracetamol (10). no association between bladder cancer risk and metamizole regular use was found among slow, intermediate and rapid acetylators (35).…”
Section: Genotoxicitymentioning
confidence: 89%
“…Formation of n-nitroso compounds (noc) by reaction with nitrite has been found to occur for diclofenac, metamizole, indomethacin, and paracetamol (10). no association between bladder cancer risk and metamizole regular use was found among slow, intermediate and rapid acetylators (35).…”
Section: Genotoxicitymentioning
confidence: 89%
“…34 In a population based case-control study conducted in Canada, a higher risk of bladder cancer (OR 5 1.5, 95% CI: 1.0-2.3) was observed with regular use of aspirin in men, 32 but no association in women (RR 5 1.1, 95% CI: 0.5-2.4). 32 Two population based case-control studies found inverse associations between regular use of aspirin and bladder cancer risk.…”
Section: Discussionmentioning
confidence: 98%
“…21,33 In contrast, a statistically nonsignificant positive association was observed between regular aspirin use and risk of bladder cancer in men in a third study, 32 and no association was observed in a fourth study on regular aspirin use. 34 In one prospective study conducted in NHANES I and NHANES II, aspirin use was associated with a statistically significant greater risk of bladder cancer mortality in women, although case numbers for women were small (N 5 15). 35 The association between acetaminophen, a major metabolite of phenacetin and bladder cancer risk has also been examined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Quinone diimine intermediates might be expected to cause cellular toxicity as shown for the quinone imine intermediates formed with acetaminophen and diclofenac [26,27]. There is some evidence that the polymorphic GSTP1 isoform might be involved in this pathway [28][29][30]. According to our understanding of the balance between the metabolic toxification and detoxification of flupirtine (Figure 1), we reasoned that subjects who were slow acetylators of NAT2 and carriers of variant alleles of UGT1A1 and GSTP1 would be more prone to flupirtine-induced liver injury because the net generation of reactive diimines would be greater than in subjects bearing wild-type enzymes.…”
Section: Introductionmentioning
confidence: 99%